2017
DOI: 10.1159/000477814
|View full text |Cite
|
Sign up to set email alerts
|

Chrysophanol Suppressed Glutamate-Induced Hippocampal Neuronal Cell Death via Regulation of Dynamin-Related Protein 1-Dependent Mitochondrial Fission

Abstract: Chrysophanic acid, or chrysophanol, is an anthraquinone found in Rheum palmatum, which was used in the preparation of oriental medicine in ancient China. The hippocampus plays a major role in controlling the activities of the short- and long-term memory. It is one of the major regions affected by excessive cell death in Alzheimer's disease. Therefore, neuronal cell-death modulation in the hippocampus is important for maintaining neuronal function. We investigated chrysophanol's effects on glutamate-induced hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…[ 38 ] Chrysophanol can inhibit neuronal cell death by regulating anti‐apoptotic and pro‐apoptotic factors in hippocampal neurons, down‐regulate Drp1 (S637) dephosphorylation and intracellular ROS accumulation. [ 39 ] Our study found that Chrysophanol could improve memory ability of d ‐galactose and Aβ 25‐35 induced AD rat model correlating with inhibiting tau hyperphosphorylation and the CaM‐CaMKIV signal pathway in hippocampus. [ 40 ] Chrysophanol exerts neuroprotective effects by reducing the neurological deficits, cerebral oedema and BBB destruction, and down‐regulating the levels of NALP3, caspase‐1 and IL‐1β, which might be involve in the inhibition of NALP3 inflammasome activation.…”
Section: Quinones and Its Role In Admentioning
confidence: 89%
“…[ 38 ] Chrysophanol can inhibit neuronal cell death by regulating anti‐apoptotic and pro‐apoptotic factors in hippocampal neurons, down‐regulate Drp1 (S637) dephosphorylation and intracellular ROS accumulation. [ 39 ] Our study found that Chrysophanol could improve memory ability of d ‐galactose and Aβ 25‐35 induced AD rat model correlating with inhibiting tau hyperphosphorylation and the CaM‐CaMKIV signal pathway in hippocampus. [ 40 ] Chrysophanol exerts neuroprotective effects by reducing the neurological deficits, cerebral oedema and BBB destruction, and down‐regulating the levels of NALP3, caspase‐1 and IL‐1β, which might be involve in the inhibition of NALP3 inflammasome activation.…”
Section: Quinones and Its Role In Admentioning
confidence: 89%
“…found that chrysophanol (10 μ m ) inhibited LPS‐induced BV‐2 murein microglial cell inflammatory response by down‐regulating dynamin‐related protein 1 (Drp1) (S637) dephosphorylation to inhibit the production of pro‐inflammatory mediators and cytokines via regulation of mitogen‐activated protein kinase (MAPK), nuclear factor‐jB (NF‐jB)and reactive oxygen species (ROS) generation. Similarly, for treating AD, researchers have found that chrysophanol could prevent excessive mitochondrial division in hippocampal neurons by inhibiting dephosphorylation of Drp1 . Moreover, Wang et al .…”
Section: Pharmacologymentioning
confidence: 99%
“…Other reports suggest that dephosphorylation of Drp1 at Ser‐637 can trigger increased mitochondrial division by calcium‐calmodulin kinase (CaMKIIα) after the hypoxic precondition and glutamate treatment leading to necroptosis in CA1 neurons, suggesting that dephosphorylation of Drp1 at Ser‐637 reverses the protective effect toward mitochondrial fission, which was mediated by phosphorylation at Ser‐637, indicating the same function in mitochondrial dynamics with phosphorylation at Ser‐40, 44, 579, 585, 592, and 616. Hence, it is necessary to elucidate whether the stimulative role of the Siah2/AKAP1 pathway in mitochondrial division and neuronal cell apoptosis was mediated by dephosphorylation at Ser‐637, but this remains unclear (Chae et al, ; Chen et al, ; Flippo et al, ; H. Kim et al, ; Zhan et al, ). The function of phosphorylation at Ser‐656 is much similar to Ser‐637, because Slupe et al found that the PKA‐mediated phosphorylation of Drp1 at Ser‐656 can decrease the Drp1 activity which denotes decreased mitochondrial fission events of mitochondria causing a protective effect of the neuronal system, whereas dephosphorylation of Drp1 at Ser‐656 mediated by protein phosphatase 2A (PP2A)/calcineurin (CaN) increases the activity of Drp1 causing neuronal death after oxygen‐glucose deprivation (OGD) treatment.…”
Section: Posttranlational Modification Of Drp1 In Neural System Dysfumentioning
confidence: 99%
“…According to Kim et al's report,Siah2 (a ubiquitin ligase) can inhibit the expression of AKAP1 by decreasing the expression of protein kinase A (PKA) and FIS1-Drp1 interaction causing increased mitochondrial division finally leading to neural cell apoptosis. Other reports suggest that dephosphorylation of Drp1 at Ser-637 can trigger increased mitochondrial division by calciumcalmodulin kinase (CaMKⅡα) after the hypoxic precondition and glutamate treatment leading to necroptosis in CA1 neurons, suggesting that dephosphorylation of Drp1 at Ser-637 reverses the protective effect toward mitochondrial fission, which was mediated by phosphorylation at Ser-637, indicating the same function in mitochondrial dynamics with phosphorylation at 44,579,585,592,and 616. Hence, it is necessary to elucidate whether the stimulative role of the Siah2/AKAP1 pathway in mitochondrial division and neuronal cell apoptosis was mediated by dephosphorylation at Ser-637, but this remains unclear (Chae et al, 2017;Chen et al, 2015;Flippo et al, 2018; H. Kim et al, 2011;Zhan et al, 2018). The function of phosphorylation (Table 1) effect in the neural system (Dickey & Strack, 2011;Slupe et al, 2013; Table 1).…”
Section: Phosphorylation Of Drp1mentioning
confidence: 99%